Scientific American. – 1871. – Vol. 25, № 18 - б/а (New York. Munn & Company, 1871)
A weekly journal of practical information, art, science, mechanics, chemistry and manufactures.
З фонду Центральної наукової бібліотеки Харківського національного університету імені В.Н. Каразіна.
Keywords: Research Subject Categories::SOCIAL SCIENCES::Other social sciences::Mass communication; Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::History subjects::History of science and ideas; October 28, 1871